Auld Lang Syne A Song and its Culture - Grant, M.J (Open Book Publishers, 2021)
In Auld Lang Syne: A Song and its Culture, M. J. Grant explores the history of this iconic song, demonstrating how its association with ideas of fellowship, friendship and sociality has enabled it to become so significant for such a wide range of individuals and communities around the world. This engaging study traces different stages in the journey of Auld Lang Syne, from the precursors to the song made famous by Robert Burns to the traditions and rituals that emerged around the song in the nineteenth and early twentieth centuries, including its use as a song of parting, and as a song of New Year. Grant's painstaking study investigates the origins of these varied traditions, and their impact on the transmission of the song right up to the present day. Grant uses Auld Lang Syne to explore the importance of songs and singing for group identity, arguing that it is the active practice of singing the song in group contexts that has made it so significant for so many. The book offers fascinating insights into the ways that Auld Lang Syne has been received, reused and remixed around the world, concluding with a chapter on more recent versions of the song back in Scotland. This highly original and accessible work will be of great interest to non-expert readers as well as scholars and students of musicology, cultural and social history, social anthropology and Scottish studies. The book contains a wealth of illustrations and includes links to many more, including manuscript sources. Audio examples are included for many of the musical examples. Grant's extensive bibliography will moreover ease future referencing of the many sources consulted.